The evolution of tamiflu synthesis, 20 years on: advent of enabling technologies the last piece of the puzzle? - Sagandira, Cloudius R.; Mathe, Francis M.; Guyo, Upenyu; Watts, Paul (Elsevier, 2021)
Influenza is a serious respiratory disease responsible for significant morbidity and mortality due to both annual epidemics and pandemics; its treatment involves the use of neuraminidase inhibitors. ( )-Oseltamivir phosphate (Tamiflu) approved in 1999, is one of the most potent oral anti-influenza neuraminidase inhibitors. Consequently, more than 70 Tamiflu synthetic procedures have been developed to date. Herein, we highlight the evolution of Tamiflu synthesis since its discovery over 20 years ago in the quest for a truly efficient, safe, cost-effective and environmentally benign synthetic procedure. We have selected a few representative routes to give a clear account of the past, present and the future with the advent of enabling technologies.